The Tourism Business Industry of the Municipality of Tanay, Rizal, Philippines: An Assessment on Human Resource and a Province-Wide Market Research - Aguilar, Mark Gabriel Wagan; Limpot, Rose Ann; Macasinag, Paul Haidriane (Journal of Tourism Management Research, 2020)
This study assessed the Tourism Industry of the Municipality of Tanay, Rizal as an emerging Ecotourism destination with emphasis on the marketability of tourism products, expertise of human resource, and the tourism development initiatives of the local government. Results show that with the success of Palaya Nature Farm, the Municipality has a potential to become a center of farm tourism in the province. The province has been determined as a primary market for boutique hotels with affordable rates and offers resort type amenities. It was also found out that the market prefers tourism businesses located in commercial zones where restaurants, tourism destinations, and hotels are near to each other. People in the province are adventurous and are into nature-based destinations, while in regards of restaurants, casual dining that offers Korean and/or Filipino cuisines are preferred. Travel agencies are also likely to succeed in the province as the market favors seeking assistance for their travels than preparing it on their own. Given the importance of the human resource in the success of the Industry as primary provider of the service, it was found out that intensive training and education is needed for the local community of Tanay, Rizal, as it shows that the level of expertise they have towards the industry operations is poor.